1991
DOI: 10.1007/bf01961160
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral breast cancer: one disease or two?

Abstract: Our purpose was to determine whether bilateral breast cancer depends upon genetic predisposition to multiple tumors or, alternatively, represents two independent sporadic events. Biological concordance of hormone receptors and histopathology in bilateral tumors, family history of breast cancer, age at diagnosis, and survival were evaluated in 88 patients. The immunoreactivity of paired tumors from 51 patients to six different immunocytochemical markers was compared. Neither histologic patterns nor immunocytoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
39
0
7

Year Published

1995
1995
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 40 publications
6
39
0
7
Order By: Relevance
“…See Table 1 for case numbers and a detailed description of the genomic imbalances. supporting the conclusion that most patients with bilateral breast carcinomas have two different diseases (Dawson et al, 1991;Sterns and Fletcher, 1991;Pandis et al, 1995;Shibata et al, 1996;Imyanitov et al, 2002). This notwithstanding, one of the patients presented two bilateral lobular carcinomas sharing all five genomic imbalances by CGH, strongly arguing that one tumour must have metastasised to the contralateral breast, as we have also seen occasionally before (Pandis et al, 1995).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…See Table 1 for case numbers and a detailed description of the genomic imbalances. supporting the conclusion that most patients with bilateral breast carcinomas have two different diseases (Dawson et al, 1991;Sterns and Fletcher, 1991;Pandis et al, 1995;Shibata et al, 1996;Imyanitov et al, 2002). This notwithstanding, one of the patients presented two bilateral lobular carcinomas sharing all five genomic imbalances by CGH, strongly arguing that one tumour must have metastasised to the contralateral breast, as we have also seen occasionally before (Pandis et al, 1995).…”
Section: Discussionsupporting
confidence: 77%
“…The increased emphasis in recent years on breast-sparing surgical treatment (Holland et al, 1985;Fisher, 1992;Connolly et al, 1995) has made it more clinically important to know whether multiple, ipsilateral breast carcinomas represent several primary tumours (multicentricity) or intramammary dissemination of a single carcinomatous process (multifocality). The fundamental biological interest of the issue is also profound, as it is also for bilateral breast carcinomas (Dawson et al, 1991;Sterns and Fletcher, 1991): are they two separate primary tumours or the metastasis from one breast to the other? Several criteria have been suggested to discriminate multiple primary tumours from metastatic lesions, including different histological growth patterns, the presence of in situ components in both tumours (for both ipsilateral and bilateral lesions), and localisation in different quadrants or more than 5 cm apart (for ipsilateral tumours; Dawson et al, 1991Dawson et al, , 1995Sterns and Fletcher, 1991;Dawson, 1993).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4 -6,44 Some authors have considered the contralateral synchronous tumor to be an independent lesion from the primary tumor (multiclonal origin theory), 3,4,7 whereas others considered SBIBC to be secondary to the metastatic spread from the opposite breast (single-clonal origin). 12,13 Dissimilarity in histology between SBIBC in the same patient was often cited in support of the independent primaries theory.…”
Section: Discussionmentioning
confidence: 99%
“…4 -6 The demonstration of different histopathologic characteristics of synchronous tumors in the left and right breasts and the presence of an in situ component in both types of tumors have been considered to be indicative factors of an independent development. 3,4,7 Other authors have shown positive correlations in histologic subtype, 8,9 tumor grade, 10 and hormone receptor status 4,11 between the two tumors and, based on these similarities, have suggested either a single cell origin with a secondary metastatic spread of cancer cells to the opposite breast 12,13 or a particular hormonal environment favoring similar biologic and pathologic features in different tumor foci of both breasts. 11 The current study had two goals.…”
mentioning
confidence: 99%